2003
DOI: 10.1021/ma0214207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Photoresponsive Polymers Containing Trifluoromethyl-Substituted Norbornadiene Moieties

Abstract: Polymers containing trifluoromethyl (CF 3 )-substituted donor-acceptor NBD moieties in the side chain or in the main chain were synthesized by substitution or addition with CF r NBD-carboxylic acid derivatives, or by polycondensation of CFrNBD-dicarboxylic acid derivatives, and the durability of the resulting polymers was examined.Photochemical valence isomerization between norbomadiene (NBD) and quadricyclane (QC) is of interest as a solar energy conversion and storage system, I because photoenergy can be sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…As shown in Figure 4 for polymer P1b, the absorption maximum at 278 nm decreases gradually on irradiation indicating a good conversion of the NBD into QC after 20 min. In addition, and as it is reported in the literature,19, 21, 31, 32 an isosbestic point at 228 nm was observed. This phenomenon, which was observed for all the samples means that the photochemical valence isomerization of the NBD units of polymer chains to the corresponding QC groups occurred selectively without side reactions.…”
Section: Resultssupporting
confidence: 85%
“…As shown in Figure 4 for polymer P1b, the absorption maximum at 278 nm decreases gradually on irradiation indicating a good conversion of the NBD into QC after 20 min. In addition, and as it is reported in the literature,19, 21, 31, 32 an isosbestic point at 228 nm was observed. This phenomenon, which was observed for all the samples means that the photochemical valence isomerization of the NBD units of polymer chains to the corresponding QC groups occurred selectively without side reactions.…”
Section: Resultssupporting
confidence: 85%
“…Photoisomerizations of organic dyes have been widely used as a means to record optical data. In particular, photoisomerization of norbornadiene and its derivatives (N, see scheme ) leading to quadricyclane and its derivatives (Q, see scheme ) has been deeply studied169–172 and polymeric materials containing N derivatives (both as covalently bonded pendant groups or simply added to transparent amorphous phases) have been investigated for optical waveguides (utilizing photoinduced refractive index changes) and for data storage 173–177. However, in all these optical materials there is a complete disorder in the spatial disposition of the photoisomerizing molecules.…”
Section: Functional Materials Based On Cocrystalline Polymer Phasesmentioning
confidence: 99%
“…[10][11][12][13] Nishikubo et al [14][15][16][17] reported that polymers containing certain norbornadiene (NBD) moieties in the main and side chains showed high photochemical reactivity, and had a high photo-energy storage capability. NBD is converted to quadricyclane (QC) under UV irradiation, and the resulting polymers are expected to be good photo-energy transformation systems.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%